Macroeconomic Imbalances and the Euro Zone. Alternative Views - Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Macroeconomic imbalances (MI) play a prominent role in the "consensus narrative" of the crisis of the Euro Zone (EZ). Accordingly, the package of governance reforms undertaken by the EZ countries amid the crisis includes the Macroeconomic Imbalances Procedure (MIP) to be enacted by the Commission. The whole approach has raised various critical and alternative views. These are examined distinguishing between the "domestic" and "external" dimension of MI, and the controversial issues are identified with reference to the MI relevance, their causes and connections with the crisis, and their policy implications.
Keywords: 330